Computer Simulation of 122 mm Ballistic Missile with a Modernized Rocket Motor - Bogdan ZYGMUNT; Krzysztof MOTYL (Problemy Mechatroniki)
Technological changes have been proposed for a rocket motor 122 mm Grad missile, consisting in the exchange of homogeneous type of rocket propellant into the propellant with significantly increased calorific value and the higher unit pulse. A mathematical-physical model of a 122 mm missile was built, taking into account the aerodynamic, geometric, mass and inertia properties. The model was implemented in a MathCAD14 simulation program. Numerical analysis of primary flight Grad missile with a modernized driving unit has been performed and compared with the existing driving unit and driving unit of the Phoenix missile. The results of computer simulation are shown in the form of graphs.